2022
DOI: 10.1039/d2ta04436f
|View full text |Cite
|
Sign up to set email alerts
|

Robust and promising hydrogen and oxygen evolution reactions by a nanostructured bifunctional FeCoPd alloy electrocatalyst

Abstract: Herein, we developed trimetallic FeCoPd polyhedral alloy nanoparticles (NPs) as a new highly efficient and promising bifunctional electrocatalyst for hydrogen and oxygen evolution reaction (HER, OER). The as-synthesized polyhedral NPs...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…The inverted burette method was used to measure the amount of generated oxygen volumetrically during this time interval. The calculated amount was compared to the actually generated amount, and the Faraday efficiency was found to be about 87% (Figure f; see the Supporting Information for the equation) …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inverted burette method was used to measure the amount of generated oxygen volumetrically during this time interval. The calculated amount was compared to the actually generated amount, and the Faraday efficiency was found to be about 87% (Figure f; see the Supporting Information for the equation) …”
Section: Results and Discussionmentioning
confidence: 99%
“…The calculated amount was compared to the actually generated amount, and the Faraday efficiency was found to be about 87% (Figure 5f; see the Supporting Information for the equation). 58 On the basis of the experimental evidence on this novel electrocatalyst and its superior OER rate, a mechanistic study is also performed. On the basis of literature reports and considering *OH and/or *O and/or *OOH is/are the adsorption species on the single active sites in alkaline condition, the following mechanism steps are considered for OER: 6,49 M OH MOH e + +…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Several new classes of compounds have emerged as efficient electrocatalysts for oxygen evolution reactions. Recently, there has been comprehensive research on the transition metal-based electrocatalysts including Fe, Co, Ni, Zn, and Cu for use in OER. In recent years, transition metal-based layered double hydroxides (LDHs) have garnered attention for their potential use in energy conversion and storage due to their excellent catalytic performance in oxygen evolution reactions. Prior to the discovery of LDHs, other layered structures such as NiO/NiOOH, Fe­(OH) 2 /FeOOH, NiCo 2 O 4 , and NiFe 2 O 4 were found to have good oxygen evolution reaction performance in alkaline media.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Kumar et al have shown that polyhedral FeCoPd NPs with octahedral and cuboctahedral shapes should expose 111 and 100 facets for an effective catalytic reaction when crystallized in a Pd-fcc structure. 10 Wang et al have experimentally demonstrated that the exceptional HER activity of mesoporous Au/Rh core−shell nanowires is mostly a result of the improved electronic structure, which has increased active surface areas and optimized intermediate adsorption energies on catalysts. 19 Duan et al have shown that Rh 2 P nanocrystals with P-rich surfaces exhibit outstanding catalytic activity for the electrochemical HER in acidic media.…”
mentioning
confidence: 99%
“…Among them, the most promising, environmentally friendly, and environmentally sustainable method of producing hydrogen and oxygen is known as the electrocatalytic water-splitting reaction. , Water is electrolyzed using two half-cell processes, the HER and the OER, which take place at the cathode and anode, respectively . Multiple electron-coupled transfer processes were used in these reactions, which require highly active catalysts to reduce the significant overpotential given by electrocatalysis . An excellent catalyst must operate admirably in terms of the HER with the lowest overpotential and highest stability.…”
mentioning
confidence: 99%